Pharmacokinetics and metabolism of the methyl-branched fatty acid (BMIPP) in animals and humans - Kropp, Joachim; Eisenhut, Michael (Journal of nuclear medicine, 1999)
The aim of this study was to further characterize the major metabolite of 15-(p-iodophenyl)-3-(R,S)-methylpentadecanoic acid (BMIPP). Methods: Radioactive components of 131I-BMIPP were evaluated in Langendorff-perfused rat hearts, as well as in blood samples from 20 patients after injection of 123I-BMIPP. Rat hearts were perfused with pH 7.4 Krebs-Henseleit buffer with or without 0.4 mmoI/L bovine serum albumin (BSA) or 0.4 mmoI/L palmitate. Lipids were Folch extracted and hydrolyzed from samples of the outflow, as well as from homogenized hearts. Radioactive components were determined by thin-layer chromatography (TLC) and high-performance liquid chromatography (HPLC) analyses. The major metabolite of BMIPP was then further characterized by electrospray mass spectrometry. Results: The rat heart perfusate showed one major polar metabolite observed by TLC (Rf = 0.35; solvent = benzene-dioxane-acetic acid 80:18:2). The addition of BSA/palmitate to the perfusate buffer significantly increased back diffusion of BMIPP (Rf = 0.55), as well as reduced BMIPP uptake and metabolism. The major metabolite was identified by mass spectral analysis as 2-(piodophenyl) acetic acid (IPC2). From TLC and HPLC analyses of the serum lipids obtained from patients, the same metabolite could be identified with levels increasing overtime (0%, 5.2% and 11.8% of the injected dose; 3 min, 20 min and 3 h postinjection, respectively). In addition to the identification of unmetabolized BMIPP (53.9%), the rat heart lipid hydrolysate also contained α-methyl-14-(p-iodophenyl)tet radecanoic acid (20.8%), 12-(p-iodophenyl)-substituted-dodecanoic (17.1%), -hexanoic acid (5.2%) and IPC2 (1.1%). Conclusion: The animal results show the complexity of uptake, metabolism and release of BMIPP from which a part is metabolized through α- and subsequent ß-oxidation to the final IPC2 metabolite as confirmed by mass spectral analysis. The results from patient studies suggest that the slow myocardial washout observed in vivo after intravenous administration of BMIPP may represent a similar process, because both unmetabolized BMIPP and the final metabolite were also identified in serum samples.
Gesehen am 09.02.2021